Judicial Dispute Resolution : New Roles for Judges in Ensuring Justice. - Susskind, Lawrence (Anthem Press, 2023)
This book describes the ways in which judges, using judicial dispute resolution (JDR), have been facilitating problem-solving among litigants, and in the process ensuring more just outcomes. JDR is similar to mediation, alternative dispute resolution (ADR),as it is sometimes called, but it is provided by a judge, not a private mediator.